Impact of organisational culture on Malaysian international contractors’ bidding decisions / Low Wai Wah - Low, Wai Wah (2015)

(untitled)
With the rapid urbanisation and globalisation, developing countries contractors start to venture into overseas markets. These contractors are exposed to various types of international risks especially external risks. International risks are not merely serious threats to existing and future international contractors but they are critical decision criteria in decision making. According to the previous literature, external risks are considered as the main determinant in bidding and overseas venture decisions. However, not all decisions are made in a logical and rational manner especially during uncertainty and risky situations. This could be explained by culture that corrupt the justification of information process. Although the impact of culture on decisions is known, yet, the effect of organisational culture on international bidding decisions to date is under-research especially in the construction sector. The aim of this study was to develop a conceptual model to illustrate the relationship interaction between organisational culture and international bidding decisions in response to the political (including legal risk) and economic risks. The objectives of the research were: (1) to identify organisational culture dimensions that are currently practising by international contractors; (2) to identify the maximum risk tolerance level of international contractors in international bidding decisions in response to political (including legal risk) and economic risks; (3) to explore empirically the relationships between organisational culture and international bidding decisions in response to political (including legal risk) and economic risks; and (4) to develop an international bidding decision model based on organisational culture perspective. The model was tested empirically through a mixed research strategy. The focus of this research was international contractors in Malaysia. Firstly, a preliminary mini case studies was conducted to test the relevancy of the impact of the identified organisational culture variables on international risk decisions. Thereafter, the proposed conceptual model was tested through the questionnaire survey. The quantitative findings were then further interpreted by interviews with experienced industry professional and followed by a model validation survey by industry experts. Based on the predictive model, goals, involvement, values, guanxi, strategy and capability orientations play a more critical role on international bidding decisions compared to hierarchy and adaptability orientations. Goals and strategy orientations contribute greater influence on international bidding decisions in response to the political risk. While, goals and guanxi orientations cast the greater influence on economic risk-related international bidding decisions followed by involvement, values and capability orientations. This study found that organisational culture cast the influence on international bidding decisions, yet, it is not the dominant cause especially in risk decisions. In conclusion, it can be construed that organisational culture is not merely impinge on the degree of internationalisation of an organisation but it represents the organisational capability in response to the risks of the host countries. In summary, the model contributes to a greater understanding of the effect of organisational culture on two (2) major types of international risk bidding decisions, namely, political and economic risks.